The role of mitochondrial introgression in illuminating the evolutionary history of Nearctic treefrogs. (7th August 2014) - Bryson, Robert W.; Smith, Brian Tilston; Nieto‐Montes de Oca, Adrian; García‐Vázquez, Uri Omar; Riddle, Brett R.
<x xml:space="preserve">Abstract</x> Inferring the evolutionary history of lineages often becomes difficult when gene histories are in conflict with each other. Introgression, for example, can cause DNA sequences from one species to be more similar to sequences of a different species and lead to incongruence amongst gene trees. However, incorporating congruent and incongruent locus‐specific phylogenetic estimates with the geographical distribution of lineages may provide valuable insight into evolutionary processes important to speciation. In this study, we investigated mitochondrial introgression within the Hyla eximia group to better understand its role in illuminating the evolutionary history and phylogeography of these treefrogs. We reconstructed and compared the matrilineal history of the Hyla eximia group with estimates of evolutionary history inferred from nuclear genes. We tested for introgression within the mitochondrial and nuclear genes using a posterior predictive checking approach. Reconstructions of the species tree based on the mitochondrial DNA (mtDNA) and nuclear DNA data were strongly discordant. Introgression between lineages was widespread in the mtDNA data set (145 occurrences amongst 11 of the 16 lineages), but uncommon in the nuclear genes (12 occurrences amongst four of the 16 lineages). Nonetheless, the geographical structuring of mtDNA within species provides valuable information on biogeographical areas, ancient areas of hybridization, and unique histories of lineages within the H. eximia group. These results suggest that the combination of nuclear, mitochondrial, and spatial information can provide a more complete picture of 'how evolutionary history played out', particularly in cases where mitochondrial introgression is known to occur. © 2014 The Linnean Society of London